Current and future challenges in starch research. (August 2021) - Hamaker, Bruce R
Highlights: Although starch seems simple, it is composed of complex and huge polymers. Amylopectin internal structure is not resolved, hampering functional understanding. Starchy foods are viewed negatively, but research shows 'quality' is the issue. Challenges for the future include better structure-function understanding. Opportunities for precise and stable starch functionalities, and healthier foods. Abstract : Even though starch seems a simple carbohydrate, composed only of glucose connected by two types of linkages, it has an amazing complexity related to its branched structure and extremely large size. Today, there are still unanswered questions that present challenges to the starch research field. Even though advances have been made in correlating starch amylopectin and amylose fine structural feature to functional properties, such as texture or digestibility, the form of the internal architecture of amylopectin is still not agreed upon. The future holds challenges in further resolving structure-function relationships of starch, and to understand and implement ways to improve the healthiness of starchy foods.